Princes of Igboland: inchoate feudalization, feudal masculinity and postcolonial patriarchy in Ifeoma Okoye's radical feminist narratives. Issue 1 (2nd April 2020) - Mayer, Adam
ABSTRACT: Space for emancipatory projects during military rule in Nigeria shrinks considerably (1983–1999, with short interruptions). This affects anti-feudalist initiatives and radical feminist movements equally. Ifeoma Okoye, the preeminent socialist-feminist writer of Igboland, publishes novels and short stories in these years that deal with women's lives and that attack post-colonial patriarchy. Her novel Men Without Ears also uncovers the mechanisms by which processes of feudalization come to characterize ethnic Igbo regions that hitherto had had no traditional rulers. Okoye in the novel weaves a narrative around a particularly toxic kind of masculinity, feudal masculinity, which imprints the newly instituted faux Igbo royal and faux Igbo feudatory. In Okoye's world, Nigerian mainstream academic feminists, criminal uncles who try to disinherit orphans, and Igbo royalty with invented ranks but with very real thugs in their employ, all represent the comprador class that directs the developmental failure of Nigeria under military rule and beyond.